D. T. Valentine, Ordinances of the Mayor, Aldermen and Commonalty of the City of New York 235 (1859) - (:unkn) unknown (My University, 1859)
Ch. 13, § 6 : No tavern-keeper, keeper of a public house, garden or place of resort, nor any other person, shall suffer or permit any person to practice with or fire off any pistol, gun, fowling-piece or other fire-arms, in or upon his or her premises, nor shall suffer or permit any pistol gallery, erected in his or her house, or upon his or her premises, to be used for the purpose of practicing with any pistol gun, fowling-piece or other fire-arms, upon the first day of the week, called Sunday, under the penalty of fifty dollars for each offense, to be sued for and recovered from the person keeping such public house, tavern, public garden, pistol gallery, place of resort or premises;
Keywords: DISCHARGE; SHOOTING RANGES OR GALLERIES